From doom spending to smart investing: Financial literacy of gen z and gen alpha towards becoming excellent accountants - Riyan Harbi Valdiansyah; Delina Dwi Indah Sari (Pengmasku, 2026)
This Community Service Program (PKM) aims to strengthen financial literacy and accounting professionalism among students of SMK Letris Pamulang, particularly Generation Z and Alpha who are digital natives. The main objective is to equip students with critical awareness of distinguishing needs from wants and mastery of digital investment instruments as preparation for the challenges of the Society 5.0 era. The method employed was a two-hour interactive seminar held on November 14, 2025, involving 91 accounting students (22 male and 69 female) from grades X–XII. The seminar emphasized the transformation of accountants’ roles from traditional data processors to strategic business advisors and reliable technology partners. The findings revealed that 58% of students intended to pursue higher education, while 42% planned to enter the workforce directly. Feedback forms using a Likert scale (1–6) showed high scores ranging from 4.38 to 5.19, indicating strong relevance of the seminar content and positive impacts on students’ attitudes toward financial planning and expenditure control. The implications highlight the importance of financial literacy as a foundation for integrity and competitiveness in future accounting careers. Recommendations for future PKM include extending seminar duration, incorporating practical simulations of digital investment, expanding participant coverage across schools, and conducting longitudinal evaluations to measure long-term behavioral impacts.